2008
DOI: 10.1007/s10620-008-0290-2
|View full text |Cite
|
Sign up to set email alerts
|

It Is Possible to Classify Non-erosive Reflux Disease (NERD) Patients into Endoscopically Normal Groups and Minimal Change Groups by Subjective Symptoms and Responsiveness to Rabeprazole—A Report from a Study with Japanese Patients

Abstract: The hypothesis that non-erosive reflux disease (NERD) patients comprise various subgroups is gaining popularity. This study was conducted to investigate the possibility of categorizing NERD patients according to symptom types and response to acid-suppressive drug rabeprazole (RPZ) 10 mg/day. NERD patients were classified as grade N (endoscopically normal), M (minimal change), or erosive GERD, and answered a 51-item, yes-or-no questionnaire pre and post-treatment. Compared to erosive GERD, clear differences exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…heartburn), but do not have breaks in the esophageal mucosa (i.e. erosion or ulcer) on endoscopy [8,9]. Moreover, there is also a group of asymptomatic patients with endoscopic redness alone, not with esophageal mucosal breaks, in esophagocardial junction.…”
Section: Introductionmentioning
confidence: 99%
“…heartburn), but do not have breaks in the esophageal mucosa (i.e. erosion or ulcer) on endoscopy [8,9]. Moreover, there is also a group of asymptomatic patients with endoscopic redness alone, not with esophageal mucosal breaks, in esophagocardial junction.…”
Section: Introductionmentioning
confidence: 99%
“…6,38,39 Another study evaluated response to 4 weeks of rabeprazole 10 mg daily in patients with EE, minimal changes, and NERD. 28 In terms of heartburn, patients with minimal changes had similar response rates to patients with NERD (38.7% and 41.7%, respectively, P = 0.81) and both had a statistically lower response rate as compared with patients with EE (68.6%, P = 0.005).…”
Section: Minimal Changes and Response To Treatmentmentioning
confidence: 78%
“…However, those with minimal changes had rates of functional gastrointestinal symptoms (epigastric heaviness, constipation) that were closer to patients with NERD, than for patients with EE. 28 In conclusion, the available data are limited and contradictory regarding the physiological difference between patients with and those without minimal changes. Lack of standardized criteria for the diagnosis of minimal changes also limits comparison between studies.…”
Section: Minimal Changes and Symptomsmentioning
confidence: 97%
“…It was pointed out that regarding esophagitis, it is difficult to rely on the histopathological findings to determine grade M in non-erosive reflux disease [14,15]. It was indicated that eosinophilic esophagitis is a chronic disease caused by inflammatory conditions associated with massive eosinophilic infiltration in the epithelium of esophageal mucosa (≥15 eosinophils in high-power field) [16], and it was also indicated that it is characterized by allergic disease causing esophageal stenosis due to the fibrosis located in the submucosa of the esophagus in long-term follow-up patients who are likely to relapse.…”
Section: Second Session: Pathological Diagnosis For Inflammation and mentioning
confidence: 99%